The influence of Socio-Political Factors on Public Policies for the Supply of Drinking Water in the North-Cameroon Region. - Ngouo, Pascal; Ndjouma Wedjou, Maurice (International Journal of Scientific Research and Management (IJSRM), 2022)
Access to drinking water is today an international emergency because of multiple challenges such as the management of the Covid-19 crisis, global warming, the protection of biodiversity, etc. According to UNICEF, the lack of access to water remains the leading cause of death in the world. Faced with this challenge, Cameroon has committed its DSCE to continue its reforms to improve the management of water resources and the implementation of drinking water supply programs throughout the country. Tested by the facts and despite many investments in this sector, the lack of access to drinking water is still glaring among our populations and in particular that of the Sahelian region of the North. Our study aims to explore the influence of socio-political factors in the supply and distribution of drinking water through wells and boreholes in the department of Mayo-Louti. Based on an inductive approach and using the qualitative research method, it is underpinned by the ontology of heuristic subjectivity. The sample is structured in 4 focus groups of 3 respondents each which give a total of 12 participants. These foci are the female, the community leaders, the youth, and the policymakers. However, the sample size is determined theoretically by the saturation point following the principles of grounded theory and the data is analyzed using the process of open coding, axial coding, and selective coding. The study shows the influence of determinants such as drought, demography, housing development, partisan politics, and health on the policy of supply and distribution of drinking water in the community of Mayo-Louti. Furthermore, the research work proposes an inclusive and sustainable model for setting the agenda for water points which is based on the ethical collaboration of all stakeholders in a process of development education.